Collaborative Governance dalam Program Kampunge Arek Suroboyo Ramah Perempuan dan Peduli Anak di Rw 01, Kelurahan Kandangan, Kota Surabaya - Harsen, Rebecca Lorenzia; Shafiya, Nandina Putri; Arofah, Yayuk Nur; Myvara, Veren; Nafi'ah, Binti Azizatun (VISA: Journal of Vision and Ideas, 2025)
Violence against children in Indonesia is still a serious issue that requires deep attention. In addition to violence, the low welfare of adolescents is a serious challenge in Indonesia. Seeing the various problems experienced by children, especially at the local level, the Surabaya City Government, through the Women's Empowerment, Child Protection, Population Control and Family Planning Service (DP3AP2KB), launched the KAS-RPA (Kampung Arek Suroboyo Friendly to Women and Children) program. To optimize the implementation of the Kasrpa Program, active collaboration is needed between implementers, including the implementation of the Kasrpa Program implemented in the Kandangan RW 01 sub-district which won the General Champion "Best of the Best" in the KASRPA 2024 Pratama category. The research method used is a descriptive research method with a qualitative approach. To measure the collaboration carried out using the collaborative governance theory by (Ansell & Gash, 2008). The results of the study indicate that Collaboration between implementers in terms of Initial Conditions, Institutional Design, Facilitative Leadership, and Collaboration Process has been implemented well.